Retracted Publications of India Indexed in Web of Science: An Analytical Study - ., Dhruvakumar; Chandrashekara, M. (Journal of Information and Knowledge, 2025)
The main intent of this study is to comprehensively review the characteristics of retracted Indian research publications indexed in the Web of Science database. The research data covered is for the period from 1989 to 2023, and results reveal that a significant portion of retracted papers was published in Q1 (293, 28.2%) and Q2 (339, 32.62%) ranked journals. Over half of the retracted articles (528 or 50.82%) were published in journals with an impact factor of less than one. Chemistry and computer science are the top two subjects with the highest number of retracted articles. A notable 198 articles were retracted within a year of their publication, closely followed by 177 articles retracted within one to two years. Interestingly, 60 articles were retracted after a decade. Despite this, 1,039 articles got 17,919 citations, with an average of 17.24 citations per article. A total of 4,329 authors contributed 1,039 articles. The majority (929 articles, 89.41%) of the retracted articles were co-authored by two to ten authors and most of the articles (749) were retracted for multiple reasons. 436 articles were retracted due to plagiarism, which encompasses the duplication and plagiarism of articles, data, text, and images.